2017
DOI: 10.1007/s11837-016-2237-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Postbuild Microstructure on the Electrochemical Behavior of Additively Manufactured 17-4 PH Stainless Steel

Abstract: The additive manufacturing (AM) build process produces a segregated microstructure with significant variations in composition and phases that are uncommon in traditional wrought materials. As such, the relationship between the post-build microstructure and the corrosion resistance is not well understood. Stainless steel alloy 17-4PH is an industrially-relevant alloy for applications requiring high-strength and good corrosion resistance. A series of potentiodynamic scans conducted in a deaerated 0.5 mol/L NaCl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 21 publications
1
41
1
1
Order By: Relevance
“…The tabulation of such studies are presented in Table 4. 61,64,[73][74][75][76][77]80,[82][83]86,[95][96][97][98][99][100][101][102][103][104] Environments containing chloride ions are well known to be detrimental to the durability of stainless steels, with a number of studies tabulated above appropriately focusing on such electrolytes. 105 In a study by Ganesh, et al, 95 two batches of specimens (termed "A" and "B") were produced via DLD, by utilizing similar parameters to produce Type 316L specimens.…”
Section: Ferrous Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…The tabulation of such studies are presented in Table 4. 61,64,[73][74][75][76][77]80,[82][83]86,[95][96][97][98][99][100][101][102][103][104] Environments containing chloride ions are well known to be detrimental to the durability of stainless steels, with a number of studies tabulated above appropriately focusing on such electrolytes. 105 In a study by Ganesh, et al, 95 two batches of specimens (termed "A" and "B") were produced via DLD, by utilizing similar parameters to produce Type 316L specimens.…”
Section: Ferrous Alloysmentioning
confidence: 99%
“…The corrosion of precipitation hardened 17-4 PH (UNS S17400) stainless steels produced by SLM was investigated by Schaller, et al, 73 and Stoudt, et al, 101 in similar concentrations of NaCl solution (0.5 M and 0.6 M, respectively). Schaller, et al, analyzed the corrosion properties of SLM 17-4 PH as a function of porosity and compared the results with their wrought counterpart.…”
Section: Crackmentioning
confidence: 99%
“…The above differences in microstructure explain the changes in hardness shown in Figure 13. Previous investigations of L-PBF 17-4 PH stainless steels focused on evaluating the heat treatment response of as-built material through hardness measurements in the solutionized [27,129,136,137], solutionized and aged [27,93,129,136], and aged only conditions [27,95,96], as shown in Table 6. The L-PBF + SHT specimen exhibited higher hardness values than the As-L-PBF sample.…”
Section: Effect Of Heat Treatment On Hardnessmentioning
confidence: 99%
“…At the energy density of 104 J/mm 3 , the corrosion performance is independent of starting powder characteristics (shape and size) and atomization method (gas or water-atomization) used to produce these powders. stainless steel is used in many applications that take advantage of its high mechanical properties in combination with its excellent corrosion resistance [26], [84], [90], [101], [104], [107]. Several research studies have been carried in our group as well as literature to fabricate defect-free L-PBF parts from 17-4 PH stainless steel and enhance the resulting mechanical properties using the post-processing operations such as hot isostatic pressing (HIP) and heat-treatment [2], [3], [6], [8], [15], [32], [50], [51], [56]- [69].…”
Section: )mentioning
confidence: 99%
“…Other studies have indicated how microstructural features can also affect the corrosion properties of post-processed [32], [40]- [42]L-PBF parts [87], [109], [112], [113]. For example, Ralston and Birbilis [114] was finished by diamond polishing using a 1µm grade medium.…”
Section: )mentioning
confidence: 99%